The Video-Based Education on Complete Basic Immunization Improves Parents' Knowledge, Attitudes, and Practices Regarding Immunization - Supadmi, Woro; Nuzulan, Moh. Aji Zulfan; Cahya Putri, Ardana; Rizky Maulana, Nafta; Rahmawati, Priska Ardya; Zukhruf Saputri, Ginanjar; Gustinanda, Rizky; Qomariyah, Nurul; Ari Kristina, Susi; Naguib Ahmed Osman, Ahmed Mohamed Yehia (Clinical and Pharmaceutical Sciences Journal, 2025)
Complete basic immunization aims to establish an effective protection system and herd immunity. Factors that influence immunization programs are parents' knowledge, perceptions, and attitudes. Efforts to improve parents' understanding can be done through education using easily accessible video media. This study aims to determine the effect of complete basic immunization education based on video on parents' knowledge, attitudes, and practices regarding immunization. This study employs a quasi-experimental design with a one-group pretest-post-test design. Data collection was conducted in April 2024. A total of 361 participants were recruited for this study, with inclusion criteria including parents of children aged up to 1.5 years residing in the service area of the Public Health Center in Yogyakarta City, and who had provided informed consent. The measurement of parents' knowledge, attitudes, and practices regarding child immunization was assessed at the pre-test and post-test intervention stages, specifically on day 1 after recruitment and the post-test on day 7 after the educational intervention. The data collection instrument used a questionnaire on parents' knowledge, attitudes, and practices, which had previously undergone validity and reliability testing. Statistical data analysis used the Wilcoxon test. The level of respondents' knowledge after receiving the intervention using educational videos showed an increase in the good criteria from 80.1% to 97.2%, attitude good criteria from 83.1% to 97.0%, while practice showed good criteria from 92.8% to 96.7%. The Wilcoxon test results for knowledge and attitude showed positive ranks of 62 and 50 respondents, respectively, who experienced an increase in knowledge with a p-value of 0.000, while for complete basic immunization practices, there was an increase of 3 respondents with a p-value of 0.083. There was a significant effect of education through videos about complete basic immunization on parents' knowledge and attitudes with a p-value of 0.000, but there was no significant effect on practice.